Induction and Bypass of p53 during Productive Infection by Polyomavirus - Dey, Dilip (American Society for Microbiology, 2002)
Lytic infection by polyomavirus leads to elevated levels of p53 and induction of p53 target genes p21Cip1/WAF1 (p21) and BAX. This is seen both in polyomavirus-infected primary mouse cell cultures and in kidney tissue of infected mice. Stabilization of p53 and induction of a p53 response are accompanied by phosphorylation of p53 on serine 18, mimicking a DNA damage response. Stabilization of p53 does not depend on p19Arf interaction with mdm2. Cells infected by a mutant virus defective in binding pRb and in inducing G(1)-to-S progression show a greatly diminished p53 response. However, cells infected by wild-type virus and blocked from entering S phase by addition of mimosine still show a p53 response. These results suggest a role of E2F target genes in inducing a p53 response. Polyomavirus large T antigen coprecipitates with p53 phosphorylated on serine 18 and also with p21Cip1/WAF1. Implications of these and other findings on possible mechanisms of induction and override of p53 functions during productive infection by polyomavirus are discussed.